Finite element simulation and experimental investigation of residual stresses in selective laser melted Ti–Ni shape memory alloy - Gu, Dongdong; He, Beibei (Computational materials science, 2016)
[Display omitted] •Detailed method for the establishment of the thermal and stress model was revealed.•In-depth understanding of the residual stresses distribution during SLM of Ti–Ni powders was proposed.•The variations of residual stresses in different positions were comprehensively studied.•The corresponding experiments were conducted to verify the results of the simulation. A three-dimensional transient finite element method (FEM) model was established to predict the stress distribution of parts shaped by selective laser melting (SLM) technology, using Ti–Ni two-component powders as the raw materials. The moving heat source with a Gaussian distribution was applied in the simulation process. By simulating the laser beam scanning process, the peak values of the thermal stresses were first recorded at the onset of the first track where the first heating–cooling cycle occurred. After the whole part was cooled down, the largest residual stresses were found at the end of the first track and the last track. To verify the simulation results, the experimental investigation with the same parameters was conducted. The initial area of the first track of the fabricated part was fully dense where the residual stresses were small. The larger residual stresses obtained at the following track resulted in the formation of the cracks at the end edge of the parts, which testified that the results were in good agreement with the simulation predictions.